Mandrit: a system for automatic generation of musical visualizations for rhythm analysis - Moura, Rute; Cabral, Giordano; Almeida, Horhanna; Scholz, Ricardo (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
Faced with the representational challenge of visually communicating musical information, we developed Mandrit: a system for automatic generation of musical visualizations for rhythm analysis. It uses data extracted from MIDI files to plot graphs for different songs, representing their rhythmic signatures. The system is customizable and presents new ways to visualize pace through different metrics. We aim to encourage the discussion in this field and the development of tools to generate musical visualizations, as a means to help musicians and scholars in musical analysis, teaching, composing and complementing musical performances.